Comparison of Two Different Rapid Prototyping System Based on Dimensional Performance Using Grey Relational Grade Method. (2016) - Dixit, Nitesh Kumar; Srivastava, Rajeev; Narain, Rakesh
Abstract: In this research, an attempt has been made to find out the influence of the process parameter along with their interactions on the dimensional accuracy of part fabricated using two different rapid prototyping machines namely fused deposition modelling machine, and a low cost open source 3D printer. 3D open source printer (3D-OSP) is one of the newly developed rapid prototyping (RP) process for part fabrication. It has been observed from previous research that the contribution of parameters such as raster width, slice height, and path speed are the most significant to the dimensional accuracy of 3D open source product while raster width, slice height, and tip dimension are the most influencing factors for fused deposition modelling machine. Taguchi parameter design of experiment method has been used to find out the optimum parameters level to minimize percentage change in length (L1), length (L2) and height (H) of test specimens fabricated by each of these two rapid prototyping machines. Experimental result revels that there is different optimal parameters level setting for each dimensional characteristics namely change in length (L1), length (L2) and height (H). Therefore, grey relational method is used to obtain optimum factor level of each dimensional characteristic simultaneously. Dimensional accuracy of parts fabricated by two different technique namely 3D open source printer and fused deposition modelling machine is within a desired range. Appropriate controls of machine process parameters improve the dimensional accuracy of parts. It is concluded that a low cost 3D open source printer gave sufficient amount of part accuracy when it is compared with the industrial based fused deposition modelling machine.